Portable compact suction pad unit for parallel grippers. (16th February 2020) - Tanaka, Junya; Yamamoto, Daisuke; Ogawa, Hideki; Ohtsu, Hiroshi; Kamata, Keisuke; Nara, Kohei
Abstract : This paper proposes a portable compact suction pad unit for the parallel grippers of a mobile manipulation robot to place items for product display. In addition, this paper includes verification of the unit's mechanism. Given that robots have to hold various items, we propose an operation method by which the parallel gripper holding the compact suction pad unit switches between a pinching mode and a vacuum suction mode depending on the item being placed. The compact suction pad unit is self-contained, with all the devices necessary for the suction operation inside the unit. The suction operation is switched on and off wirelessly by an external host system controller. The compact suction pad unit produced a suction force of about 5.6 N at an allowable inclination angle of 15°. We demonstrated in a competition that our proposed operation method of the compact suction pad unit is useful by having it place a beverage in a cup with lid and a boxed lunch. GRAPHICAL ABSTRACT: